2008
DOI: 10.1017/s000711450891151x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibre and fermentability characteristics of root crops and legumes

Abstract: The dietary fibre and fermentability characteristics of local root crops and legumes were determined. Total, soluble and insoluble fibre were determined in six root crops (kamote, gabi, potato, tugi, ube, cassava) and ten legumes (mungbean, soyabean, peanut, pole sitao, cowpea, chickpea, green pea, lima bean, kidney bean and pigeon pea) using Association of Official Analytical Chemists methods. The dietary fibre from test foods was isolated and fermented in vitro using human faecal inoculum simulating conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 10 publications
4
35
3
Order By: Relevance
“…Highest reduction in TDF (35%) occurred in Isiocha while the least reduction in TDF occurred in iron beans (4%) at 75% infestation level. The TDF of the uninfested cowpeas (34-49%) was in close agreement with the range of 20.9 to 46.9 g/100 g TDF reported for a number of legumes including soybean, peanut and cowpea among others by Mallillin et al (2008). Decrease in TDF in the infested cowpea samples was attributed to feeding on the soluble portion of TDF by the insects.…”
Section: Total Dietary Fibresupporting
confidence: 85%
“…Highest reduction in TDF (35%) occurred in Isiocha while the least reduction in TDF occurred in iron beans (4%) at 75% infestation level. The TDF of the uninfested cowpeas (34-49%) was in close agreement with the range of 20.9 to 46.9 g/100 g TDF reported for a number of legumes including soybean, peanut and cowpea among others by Mallillin et al (2008). Decrease in TDF in the infested cowpea samples was attributed to feeding on the soluble portion of TDF by the insects.…”
Section: Total Dietary Fibresupporting
confidence: 85%
“…bean, pea, soybean, chickpea, lentils), mature and imature seeds are good sources of dietary fiber and isoflavonoids [31]. Mallillin et al [32] determined the total, soluble and insoluble fibre and fermentability characteristics of ten legumes mature seeds (mungbean, soyabean peanut, pole sitao, cowpea, chickpea, green pea, lima bean, kidney bean and pigeon pea) and concluded that the dietary fibre content ranged from 20.9 to 46.9 g/100g and that the best sources after in vitro fermentation using human faecal inoculum stimulating conditions in the human collon (as mmol/g/fibre isolate of acetate, propinate, butyrate produced after fibre fermentation measured by HPLC) were pole sitao and mungbean (acetate), kidney bean and pigeon pea, (propinate), and peanut and cowpea (butyrate). High-flavonol legumes include sugar snap peas and mange-tout, which were found to contain 98 and 145 µg quercetin/g respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The hypocholesterolaemic property of legumes is associated with the water-soluble fibre. Dietary fiber in legumes is not digested in the small intestine but be fermented in the colon and produces short chain fatty acids such as acetate, propionate and butyrate [172,173]; that inhibits hydroxy-3-methylglutaryl-CoA reductase, the limiting enzyme for cholesterol synthesis. Dietary fiber also decrease LDL cholesterol concentration by partially interrupting the enterohepatic circulation of bile acids via binding to bile acids in the intestines and preventing their re-absorption [174].…”
Section: Beans and Legumesmentioning
confidence: 99%